The Redox Journey of Iconic Ferrocene: Ferrocenium Dications and Ferrocenate Anions. Issue 23 (29th April 2021) - Walawalkar, Mrinalini G.; Pandey, Priya; Murugavel, Ramaswamy
Abstract : The recent discoveries of both dicationic and monoanionic ferrocene derivatives throw light on the effect of the substituents on the C5 ring as well as the choice of redox agents and solvent system in the preparation of previously believed to be difficult synthetic targets. These oxidized and reduced forms of ferrocene are of interest to spectroscopists, magnetochemists, and theoreticians.